(untitled) (Proceedings of the International Conference on Poverty and Sustainable Development, 2019)
This paper present finding that capital was not primary factor for entrepreneurial success of 43 MSME’s beneficiaries receiving Livelihood Project’ fund from UMCOR-NGO Indonesia, aftermath 2004 Indian Ocean tsunami disaster. Capital that was not supported at the same time with proper business management and entrepreneurial spirit of respective MSME’s beneficiaries resulted in extremely difficult to develop. The method of research is descriptive-quantitative. The research found that UMCOR has not properly scrutinized individual beneficiaries’ ability prior conducting entrepreneurial activities, in accordance to initial data processing of entrepreneurial success indicator. Poor intensive assistance from reliable parties towards beneficiaries’ problems solving also contributed to the burdensome. The study concludes that it is necessary to develop an assessment indicator system of entrepreneurial success within the project assessment. It allows UMCOR-NGO to alleviate obstacles and contributes substantial supports for the beneficiaries’ entrepreneurial success: to be capable of producing its contributions to economy and to society.